Ageism as a Hate Crime: The Case for Extending Aggravated Offences to Protect Age Groups. (22nd December 2020) - Goosey, Stuart
Abstract: This article argues that hate crime laws in England and Wales should be extended to protect age groups by aggravating offences that are based on or motivated by hostility to age groups. I critically assess the following arguments for this: that age-related hate crime can impose greater psychological distress than equivalent non-hate crime and this justifies the increased punishments that aggravated offences offer; that hate crime laws can justifiably protect older people because older people are relatively vulnerable to crime; that extending aggravated offences to protect age groups can justifiably punish hate crime offenders for their increased culpability in contributing to marginalisation of age groups; and creating distinct aggravated offences for age-hostile crimes has symbolic value to reflect the grave moral wrong of these crimes and to communicate that the state is committed to eradicating discrimination against age groups.